2018
DOI: 10.1039/c8cy01418c
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-catalyzed C–H activation: recent progress in heterocyclic chemistry

Abstract: Cobalt-catalyzed C–H activation has gone through some major advancements in the past couple of decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 114 publications
0
20
0
Order By: Relevance
“…Indeed, Co exhibits a comparable coordination sphere to Zn, is a cheap metal that have found ongoing developments in catalysis for example. [48][49][50][51][52] In this context, gaining a first set of structural information is undoubtedly of broad interest. The geometry of Co complexes is analyzed from solid-state data and finally compared to their Zn analogues.…”
mentioning
confidence: 99%
“…Indeed, Co exhibits a comparable coordination sphere to Zn, is a cheap metal that have found ongoing developments in catalysis for example. [48][49][50][51][52] In this context, gaining a first set of structural information is undoubtedly of broad interest. The geometry of Co complexes is analyzed from solid-state data and finally compared to their Zn analogues.…”
mentioning
confidence: 99%
“…Under the optimized conditions (Scheme 4), authors investigated the substrate scope, firstly, in regard of alkynes and found that aryl substituted terminal alkynes bearing either electron-withdrawing or -donating groups on various positions of the aromatic ring afforded products in high yields (38)(39)(40)(41)(42). Moreover, terminal alkynes with aromatic substituents like naphthyl, pyrene, and heterocycles led to high yields (43)(44)(45)(46), while terminal aliphatic substituted alkynes resulted in low to high yields (47)(48)(49)(50)(51). There were only a few examples for internal alkynes with yields being low to moderate (52,53).…”
Section: Annulations Via C(sp 2 )-H Bond Activationmentioning
confidence: 99%
“…Motivated by the above-mentioned needs, researchers have employed the use of functional groups that significantly affect C-H activation reactions. Directing groups (DG) represent an ingenious way to orchestrate and manipulate atoms towards the synthesis of important classes of organic compounds, such as pyrroles, indoles, quinolines, indolinones, and related heterocycles [44][45][46][47][48]. Transition metals can temporarily coordinate to these specific sites on the starting materials, thus leading to the formation of key intermediates that would not form otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…The capability of manganese as a promising catalyst is evident from the reports in oxidation [15], reduction [16], C‐H activation [17], coupling reactions [18], etc. In continuation of our constant interest in green reactions and earth abundant transition metal catalyzed processes, we focused on microwave (MW) reactions [19] and transition metal catalysis involving Fe [20], Co [21], Ni [22], Mn [23], and Cu [24], respectively. As an extension, we herein report the first manganese‐catalyzed strategy for N ‐aryl pyrrole synthesis using a green Clauson‐Kaas protocol under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%